Titanium carbide composite material as well as preparation method and hydrogen detection application thereof

By using titanium carbide composite materials, including Ti3C2Tx substrate and loaded Pd nanoparticles, a high sensitivity and high selectivity hydrogen sensor was prepared, which solved the application problems of existing hydrogen detection technology in room temperature environments and achieved low power consumption and high stability hydrogen detection effect.

CN119591107AActive Publication Date: 2025-03-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311168252.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-11
Publication Date
2025-03-11
Estimated Expiration
2043-09-11

AI Technical Summary

Technical Problem

The existing hydrogen detection technology has problems such as high working temperature, large power consumption, poor stability, low selectivity and low sensitivity, which limits its application in room temperature environments.

Method used

Using titanium carbide composite materials, including Ti3C2Tx substrate and Pd nanoparticles loaded on the Ti3C2Tx substrate, a high sensitivity and high selectivity hydrogen sensor was prepared by contacting and solid-liquid separation under light conditions.

Benefits of technology

It realizes high sensitivity and selectivity detection of hydrogen under room temperature environment, with low power consumption, high stability, strong adaptability, rapid response and good reversibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591107A_ABST
    Figure CN119591107A_ABST
Patent Text Reader

Abstract

The invention relates to the field of gas detection, in particular to a titanium carbide composite material, a preparation method thereof and hydrogen detection application. The titanium carbide composite material comprises a Ti3C2Tx substrate and Pd nanoparticles loaded on the Ti3C2Tx substrate, the Ti3C2Tx substrate is of a multi-layer structure, and at least part of the Pd nanoparticles are loaded between layers of the multi-layer structure of the Ti3C2Tx substrate. The hydrogen sensor using the titanium carbide composite material disclosed by the invention can be used for detecting hydrogen with high sensitivity and high selectivity in a room-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of gas detection, and in particular to a titanium carbide composite material and a preparation method thereof, as well as hydrogen detection applications. Background Art

[0002] Hydrogen has unique characteristics such as high combustion heat, environmental protection, and abundant reserves. It is an important clean new energy source for the next generation. However, the flammability and explosion range of hydrogen energy have largely hindered the application of hydrogen energy in modern energy systems, which requires high-performance sensors to avoid the hazards caused by hydrogen leakage. At present, most hydrogen sensors are based on metal oxide semiconductors (MOS). MOS-based hydrogen sensors have the advantages of high sensitivity, short response time, and low detection limit, but their application is limited due to high operating temperature and high power consumption. Pure palladium (Pd) or its alloy nanostructures have low power consumption in hydrogen detection, but have defects such as high cost and poor mechanical properties. These limit their large-scale popularization and application. In this context, it is of great significance to design a hydrogen sensing material that can meet room temperature availability and strong adaptability. Summary of the invention

[0003] The purpose of the present invention is to overcome the problems of high operating temperature, high power consumption (metal oxide semiconductor substrate hydrogen sensor), poor stability, low selectivity and low sensitivity in the existing hydrogen detection technology, and to provide a titanium carbide composite material, a hydrogen sensor and a preparation method and application thereof. The hydrogen sensor using the titanium carbide composite material of the present invention can detect hydrogen with high sensitivity and high selectivity at room temperature.

[0004] In order to achieve the above object, the present invention provides a titanium carbide composite material, wherein the titanium carbide composite material comprises Ti3C2T x Substrate and load on the Ti3C2T x The Pd nanoparticles on the substrate, the Ti3C2T x The substrate has a multilayer structure, and at least part of the Pd nanoparticles are loaded on the Ti3C2T x Between the layers of the base multi-layer structure.

[0005] Preferably, the multi-layer structure has 30-80 layers.

[0006] Preferably, the Ti3C2T x The substrate thickness is 5-150 nm, preferably 10-100 nm.

[0007] Preferably, the particle size of the Pd nanoparticles is 5-80 nm, preferably 5-40 nm.

[0008] Preferably, the loading amount of the Pd nanoparticles is 10-60 wt % relative to the total weight of the titanium carbide composite material.

[0009] Preferably, the Pd nanoparticles are loaded on the Ti3C2T x Substrate surface and the Ti3C2T x Between the layers of the base multi-layer structure.

[0010] According to a second aspect of the present invention, a method for preparing a titanium carbide composite material is provided, wherein the method comprises: in a light-proof condition, x After the dispersion of nanosheets is brought into contact with the Pd nanoparticles, the product after the contact is subjected to a solid-liquid separation step.

[0011] Preferably, the Ti3C2T x The dispersion of nanosheets was prepared by mixing Ti3C2T x The nanosheets are dispersed in a dispersion medium.

[0012] Preferably, by x The nanosheets are dispersed in a dispersion medium and then ultrasonicated to obtain the nanosheets.

[0013] Preferably, the ultrasonic conditions include: power of 100-800W, temperature of 0-30°C, and time of 60-600min.

[0014] Preferably, Ti3C2T x The weight ratio of the nanosheets to the dispersion medium is 1:50-100.

[0015] Preferably, the dispersion medium is one or more of water, ethanol, acetone and n-hexane.

[0016] Preferably, the dispersion medium is water and ethanol; more preferably, the volume ratio of ethanol to water is 1-5:1, and further preferably 1-3:1.

[0017] Preferably, the Pd nanoparticles are x The weight ratio of the nanosheets is 0.1-0.6:1, preferably 0.1-0.3:1.

[0018] Preferably, the contacting conditions include: temperature of 60-80° C. and time of 6-12 h.

[0019] Preferably, the solid-liquid separation is centrifugation, and the speed of the centrifugation is 3000-15000 rpm, preferably 6000-10000 rpm.

[0020] Preferably, the method further comprises the step of freeze-drying the solid phase obtained by solid-liquid separation.

[0021] Preferably, the method further comprises a step of washing with water before freeze-drying the solid phase obtained by solid-liquid separation.

[0022] Preferably, the freeze-drying conditions include: a temperature of -70 to -40°C and a time of 6 to 14 hours.

[0023] Preferably, the Ti3C2T x The nanosheets are obtained by etching the precursor Ti3AlC2 using hydrofluoric acid or fluoride salts.

[0024] Preferably, the Pd nanoparticles are reduced to H2PdC by a reducing agent. l4 It is obtained by Pd ions in solution.

[0025] Preferably, the reducing agent is one or more of hydrazine hydrate, sodium citrate, and sodium borohydride, preferably sodium citrate or sodium borohydride.

[0026] According to a third aspect of the present invention, a hydrogen sensor is provided, wherein the hydrogen sensor comprises: a sensing film formed on the surface of an electrode, wherein the sensing film contains the titanium carbide composite material described in the first aspect of the present invention or the titanium carbide composite material prepared by the method described in the second aspect of the present invention.

[0027] According to a fourth aspect of the present invention, a method for preparing a hydrogen sensor is provided, wherein the method comprises the step of coating the titanium carbide composite material described in the first aspect of the present invention or the titanium carbide composite material prepared by the method described in the second aspect of the present invention on the surface of an electrode to form a sensing film.

[0028] Preferably, the titanium carbide composite material is dispersed in an organic solvent and then ground, and the ground material is coated on the surface of the electrode to form a sensing film.

[0029] Preferably, the mass ratio of the organic solvent to the titanium carbide composite material is 1-5:1, preferably 1-3:1.

[0030] Preferably, the sensing film has a thickness of 50-2000 μm, preferably 100-1000 μm.

[0031] According to a fifth aspect of the present invention, there is provided use of the titanium carbide composite material described in the first aspect of the present invention or the titanium carbide composite material prepared by the method described in the second aspect of the present invention in preparing a hydrogen sensor.

[0032] Through the above technical scheme, the preparation method of the titanium carbide composite material of the present invention is simple to operate, has high stability, and is convenient for large-scale preparation. The prepared hydrogen sensor has the excellent performance of being able to work in a room temperature environment, having low power consumption, high stability, high selectivity, and high sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The Ti3C2T obtained in Example 1 x SEM images of nanosheets;

[0034] Figure 2 is a scanning electron microscope image of the Pd nanoparticles obtained in Example 1;

[0035] Figure 3 is a scanning electron microscope image of the titanium carbide composite material obtained in Example 1;

[0036] Figure 4 The resistance value change curves of hydrogen sensors made of different materials (Comparative Examples 1-2, Example 1) when placed in 5% concentration hydrogen respectively;

[0037] Figure 5 This is a photo of the hydrogen sensor made of the titanium carbide composite material in Example 2-4. DETAILED DESCRIPTION

[0038] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0039] A first aspect of the present invention provides a titanium carbide composite material, wherein the titanium carbide composite material comprises Ti3C2T x Substrate and load on the Ti3C2T x The Pd nanoparticles on the substrate, the Ti3C2T x The substrate has a multilayer structure, and at least part of the Pd nanoparticles are loaded on the Ti3C2T x Between the layers of the base multi-layer structure.

[0040] According to the present invention, the Ti3C2T x The substrate is a multi-layer structure. Preferably, the number of layers of the multi-layer structure may be 30-80 layers; more preferably, the number of layers of the multi-layer structure may be 40-60 layers.

[0041] In the present invention, the multilayer structure provides an ideal diffusion channel for the rapid diffusion of H2, which is beneficial to the improvement of charge migration, transmission and sensing performance.

[0042] According to the present invention, as the Ti3C2T x The substrate thickness is nanometer level. Preferably, the Ti3C2T x The substrate thickness is 5-150nm; more preferably, the Ti3C2T x The substrate thickness is 10-100 nm.

[0043] According to the present invention, the Pd nanoparticles are loaded on the Ti3C2T x The surface and interlayers of the substrate, as the particle size of the Pd nanoparticles, is preferably 5-80nm. In order to allow more of the Pd nanoparticles to be located in the layers of the multilayer structure, preferably, the particle size of the Pd nanoparticles is 5-40nm.

[0044] In the present invention, the Pd nanoparticles provide active sites required for rapid adsorption and dissociation of H2, which can synergistically accelerate the speed of response to H2.

[0045] According to the present invention, relative to the total weight of the titanium carbide composite material, preferably, the loading amount of the Pd nanoparticles is 10-60% by weight, and more preferably, the loading amount of the Pd nanoparticles is 20-30% by weight.

[0046] In the present invention, by making the content of Pd nanoparticles within the above range, sufficient interaction force can be formed between the Pd nanoparticles and H2 molecules, so as to further improve the high sensitivity to H2.

[0047] According to the present invention, preferably, the Pd nanoparticles are loaded on the Ti3C2T x Substrate surface and the Ti3C2T x The interlayer of the substrate multilayer structure. x The surface of the substrate is loaded with Pd nanoparticles, which can make H2 molecules in the air quickly gather around the titanium carbide composite material. x The interlayer loading of Pd nanoparticles on the substrate multilayer structure can further improve the sensitivity to H2 molecules. x The Pd nanoparticles loaded on the substrate surface and between the layers of the multilayer structure avoid the aggregation of Pd nanoparticles on the surface and improve the utilization rate of Pd nanoparticles. In addition, the Pd nanoparticles loaded between the layers also play a role in inhibiting the Ti3C2T x The effect of the collapse of the multi-layer structure improves the stability of the multi-layer structure.

[0048] Based on the above advantages, the titanium carbide composite material has the characteristics of high stability and high sensitivity, and has excellent performance in practical applications. It can achieve an ultra-fast response to 1 volume % hydrogen within 10 seconds at room temperature, and the detection range is 1-40 volume %.

[0049] The second aspect of the present invention provides a method for preparing a titanium carbide composite material, wherein the method comprises: in a light-proof condition, x After the dispersion of nanosheets is brought into contact with the Pd nanoparticles, the product after the contact is subjected to a solid-liquid separation step.

[0050] According to the present invention, preferably, the Ti3C2T x The dispersion of nanosheets was prepared by mixing Ti3C2T x The nanosheets are dispersed in a dispersion medium; more preferably, Ti3C2T x The nanosheets are dispersed in a dispersion medium and then ultrasonicated to obtain the nanosheets.

[0051] By combining Ti3C2T x The nanosheets are dispersed in a dispersion medium and then ultrasonicated to obtain the Ti3C2T x When the nanosheet dispersion is prepared, preferably, the ultrasonic conditions include: power of 100-800W, temperature of 0-30°C, and time of 60-600min; more preferably, the ultrasonic conditions include: power of 300-600W, temperature of 0-20°C, and time of 60-200min.

[0052] According to the present invention, preferably, Ti3C2T x The weight ratio of the nanosheets to the dispersion medium is 1:50-100; more preferably, Ti3C2T x The weight ratio of the nanosheets to the dispersion medium is 1:60-80. According to the present invention, preferably, the dispersion medium is one or more of water, ethanol, acetone and n-hexane; more preferably, the dispersion medium is water and ethanol; further preferably, the volume ratio of ethanol to water is 1-5:1; particularly preferably, the volume ratio of ethanol to water is 1-3:1.

[0053] According to the present invention, the Pd nanoparticles and the Ti3C2T x The weight ratio of the nanosheets is 0.1-0.6:1; preferably, the Pd nanoparticles and the Ti3C2T x The weight dosage ratio of the nanosheets is 0.1-0.3:1.

[0054] According to the present invention, preferably, the contacting conditions include: temperature of 60-80° C. and time of 6-12 h.

[0055] According to the present invention, preferably, the solid-liquid separation is centrifugation, and the centrifugal speed is 3000-15000 rpm, preferably, the centrifugal speed is 6000-10000 rpm.

[0056] According to the present invention, preferably, the method further comprises the step of freeze-drying the solid phase obtained by solid-liquid separation. More preferably, the method further comprises the step of washing the solid phase obtained by solid-liquid separation with water before freeze-drying;

[0057] According to the present invention, preferably, the freeze-drying conditions include: a temperature of -70 to -40°C and a time of 6 to 14 hours.

[0058] According to the present invention, the Ti3C2T x Nanosheets can be obtained by etching the precursor Ti3AlC2 using hydrofluoric acid or fluoride salts.

[0059] Preferably, the mass concentration of the hydrofluoric acid is 10-40% by weight, more preferably 20-30% by weight.

[0060] Preferably, the molar ratio of the above fluoride salt to Ti3AlC2 is 1-3:1, more preferably 1-2:1.

[0061] Preferably, the above etching conditions include: etching time of 10-48h, etching temperature of 10-70°C.

[0062] According to the present invention, the Pd nanoparticles can be reduced to H2PdC by a reducing agent. l4 It is obtained by Pd ions in solution.

[0063] According to the present invention, preferably, the reducing agent is one or more of hydrazine hydrate, sodium citrate and sodium borohydride; more preferably, the reducing agent is sodium citrate or sodium borohydride.

[0064] Since the chemical reduction process is relatively fast, in order to prevent the palladium particles from agglomerating, it is preferred to add a protective agent such as polyvinyl pyrrolidone, etc. The amount of the protective agent added can be 20-40% of the molar amount of Ti3AlC2.

[0065] Preferably, the H2PdC l4 The solvent used in the solution is one or more of tetraethylene glycol, ethylene glycol and water.

[0066] Preferably, the reducing agent and the H2PdC l4 H2PdC in solution l4 The molar ratio of may be 1-15:1, more preferably 2-8:1.

[0067] The third aspect of the present invention provides a hydrogen sensor, wherein the hydrogen sensor comprises: a sensing film formed on the surface of an electrode, wherein the sensing film contains the titanium carbide composite material described in the first aspect of the present invention or the titanium carbide composite material prepared by the method described in the second aspect of the present invention.

[0068] The fourth aspect of the present invention provides a method for preparing a hydrogen sensor, wherein the method comprises the step of coating the titanium carbide composite material described in the first aspect of the present invention or the titanium carbide composite material prepared by the method described in the second aspect of the present invention on the surface of an electrode to form a sensing film.

[0069] According to the present invention, before coating by the coating method, it is preferred to use an organic solvent (for example, ethanol, acetone, glycerin, pinene alcohol, etc.) to disperse the titanium carbide composite material and then grind it (for example, grind it in an agate mortar) to make the titanium carbide composite material evenly dispersed in the organic solvent. The mass ratio of the above-mentioned organic solvent to the titanium carbide composite material can be 1-5:1, preferably 1-3:1. Too much of the above-mentioned organic solvent will make the titanium carbide composite material dispersion too thin and unable to be coated on the electrode; too little of the above-mentioned organic solvent will make the titanium carbide composite material too thick, so that the material coated on the electrode is unevenly distributed, affecting the gas sensing performance.

[0070] In the present invention, the thickness of the sensing film may be 50-2000 μm, preferably 100-1000 μm.

[0071] The fifth aspect of the present invention provides use of the titanium carbide composite material described in the first aspect of the present invention or the titanium carbide composite material prepared by the method described in the second aspect of the present invention in preparing a hydrogen sensor.

[0072] The present invention is described in detail below by way of examples, but the present invention is not limited to the following examples.

[0073] Example 1

[0074] 1) Synthesis of Ti3C2T x Nanosheets

[0075] (1) 2 g of Ti3AlC2 powder was placed in 50 ml of hydrofluoric acid (40 mol%) aqueous solution, stirred at room temperature for 36 h, and then centrifuged. After centrifugation, the mixture was washed several times with deionized water until the pH value of the supernatant was 6.

[0076] (2) The product was washed again with deionized water, vacuum filtered through a polytetrafluoroethylene membrane with a pore size of 0.22 μm, and then dried in a vacuum drying oven at 70° C. for 8 h.

[0077] (3) The dried powder was placed in deionized water, ultrasonicated at 4°C, and then separated by a centrifuge to obtain Ti3C2Tx Nanosheets.

[0078] 2) Preparation of Pd nanoparticles by sodium citrate reduction method

[0079] (1) 1.0ml / 0.03mol / L H2PdC l4 -tetraethylene glycol solution, 1.0ml / 0.15mol / L polyvinyl pyrrolidone-tetraethylene glycol solution, 1.0ml / 0.045mol / L sodium citrate-tetraethylene glycol solution, and 7.0ml tetraethylene glycol are added to a 50ml round-bottom flask, the flask is connected to a microwave reactor, and the flask is rapidly heated for 60s under rapid stirring with a mechanical stirrer to obtain a polyvinyl alkoxide-stabilized palladium nanoparticle colloidal solution.

[0080] (2) The colloidal solution of palladium nanoparticles changes from brown to dark brown. Five times more acetone is added to the colloidal solution and allowed to stand for a period of time to obtain a viscous black precipitate (its morphology is as shown in FIG. Figure 2 Wash and dry

[0081] 3) Preparation of titanium carbide composite materials

[0082] (1) Ti3C2T x 0.5 g of nanosheets were dispersed in a dispersion medium with a V (ethanol) / V (water) ratio of 3:1 and subjected to ultrasonic treatment; the ultrasonic conditions included: power of 500 W, temperature of 20° C., and time of 120 min;

[0083] (2) adding 0.1 g of Pd nanoparticles, stirring for 2 h in the dark, and then heating at 60 °C for 6 h under reflux;

[0084] (3) performing solid-liquid separation to remove free Pd nanoparticles at a centrifugal speed of 10,000 rpm;

[0085] (4) After washing with deionized water, the resultant was freeze-dried at -50°C for 8 h to obtain a titanium carbide composite material A1.

[0086] The titanium carbide composite material prepared in Example 1 was characterized using a scanning electron microscope (brand: Hitachi, model: SU3800). x SEM images of nanosheets are shown in Figure 1 As shown, the SEM image of the Pd nanoparticles prepared in Example 1 is as follows Figure 2 As shown, the SEM image of the titanium carbide composite material prepared in Example 1 is as follows Figure 3 shown.

[0087] Depend on Figure 1 It can be seen that Ti3C2T xIt is a layered nanosheet with a thickness of about 100nm and a multilayer structure (about 80 layers); Figure 2 It can be seen that the size of Pd nanoparticles is about 5nm. Figure 3 It can be seen that Pd nanoparticles are loaded into Ti3C2T x The nanosheets' surfaces and interlayers form a composite material.

[0088] In addition, by using an energy spectrometer (brand: Hitachi, model: SU3800) to perform EDS spectrum semi-quantitative analysis, it can be known that the loading amount of the Pd nanoparticles is 20 weight % relative to the total weight of the titanium carbide composite material.

[0089] Example 2

[0090] 1) Synthesis of Ti3C2T x Nanosheets

[0091] (1) 2 g of Ti3AlC2 powder was placed in a mixed solution of 40 ml of hydrochloric acid and 3 g of lithium fluoride, stirred at 35°C for 48 h, and then centrifuged. After centrifugation, the mixture was washed several times with deionized water until the pH value of the supernatant was 6.

[0092] (2) The product was washed again with deionized water, vacuum filtered using a polytetrafluoroethylene membrane with a pore size of 0.22 μm, and then dried in a vacuum drying oven at 70° C. for 8 h.

[0093] (3) The dried powder was placed in deionized water, ultrasonicated at 4°C, and then separated by a centrifuge to obtain Ti3C2T x Nanosheets.

[0094] 2) Preparation of Pd nanoparticles by sodium borohydride reduction method

[0095] (1) 1.0ml / 0.03mol / L H2PdC l4 -tetraethylene glycol solution, 1.0ml / 0.15mol / L polyvinyl pyrrolidone-tetraethylene glycol solution, and 5.0ml / 0.02mol / L sodium borohydride-tetraethylene glycol solution were added into a 100ml round-bottom flask, and the flask was connected to a microwave reactor and rapidly stirred for 6h under a mechanical stirrer to obtain a polyvinyl alkoxide-stabilized palladium nanoparticle colloidal solution.

[0096] (2) The colloidal solution of palladium nanoparticles changes from brown to dark brown. Five times more acetone is added to the colloidal solution and allowed to stand for a period of time to obtain a viscous black precipitate (its morphology is as shown in FIG. Figure 2 Wash and dry

[0097] 3) Preparation of titanium carbide composite materials

[0098] (1) Ti3C2T x 0.5 g of nanosheets were dispersed in a dispersion medium with a V (ethanol) / V (water) ratio of 3:1 and subjected to ultrasonic treatment; the ultrasonic conditions included: power of 500 W, temperature of 20° C., and time of 60 min;

[0099] (2) adding 0.1 g of Pd nanoparticles, stirring for 2 h in the dark, and then heating under reflux at 60 °C for 5 h;

[0100] (3) performing solid-liquid separation to remove free Pd nanoparticles at a centrifugal speed of 8000 rpm;

[0101] (4) After washing with deionized water, the resultant was freeze-dried at -50°C for 8 h to obtain a titanium carbide composite material A2.

[0102] The titanium carbide composite material prepared in Example 2 was characterized using a scanning electron microscope (brand: Hitachi, model: SU3800). x The SEM image of the nanosheets shows that Ti3C2T x The layered nanosheets with a thickness of about 100 nm are multilayer structures (about 50 layers). The SEM image of the Pd nanoparticles shows that the size of the Pd nanoparticles is about 8 nm. The SEM image of the titanium carbide composite material shows that the Pd nanoparticles are loaded into the Ti3C2T x The nanosheets' surfaces and interlayers form a composite material.

[0103] In addition, it can be known from the semi-quantitative analysis of EDS energy spectrum that the loading amount of the Pd nanoparticles is 15 wt % relative to the total weight of the titanium carbide composite material.

[0104] Example 3

[0105] 1) Synthesis of Ti3C2T x Nanosheets

[0106] (1) 2 g of Ti3AlC2 powder was placed in a mixed solution of 40 ml of hydrochloric acid and 3 g of lithium fluoride, stirred at 35°C for 48 h, and then centrifuged. After centrifugation, the mixture was washed several times with deionized water until the pH value of the supernatant was 6.

[0107] (2) The product was washed again with deionized water, vacuum filtered using a polytetrafluoroethylene membrane with a pore size of 0.22 μm, and then dried in a vacuum drying oven at 70° C. for 8 h.

[0108] (3) The dried powder was placed in deionized water, ultrasonicated at 4°C, and then separated by a centrifuge to obtain Ti3C2T x Nanosheets.

[0109] 2) Preparation of Pd nanoparticles by sodium borohydride reduction method

[0110] (1) 1.0ml / 0.03mol / L H2PdC l4 -tetraethylene glycol solution, 1.0ml / 0.15mol / L polyvinyl pyrrolidone-tetraethylene glycol solution, and 5.0ml / 0.02mol / L sodium borohydride-tetraethylene glycol solution were added into a 100ml round-bottom flask, and the flask was connected to a microwave reactor and rapidly stirred for 6h under a mechanical stirrer to obtain a polyvinyl alkoxide-stabilized palladium nanoparticle colloidal solution.

[0111] (2) The colloidal solution of palladium nanoparticles changes from brown to dark brown. Five times more acetone is added to the colloidal solution and allowed to stand for a period of time to obtain a viscous black precipitate (its morphology is as shown in FIG. Figure 2 Wash and dry

[0112] 3) Preparation of titanium carbide composite materials

[0113] (1) Ti3C2T x 0.3 g of the nanosheets were dispersed in a dispersion medium with a V (ethanol) / V (water) ratio of 2:1 and subjected to ultrasonic treatment; the ultrasonic conditions included: power of 800 W, temperature of 30° C., and time of 300 min;

[0114] (2) adding 0.1 g of Pd nanoparticles, stirring for 2 h in the dark, and then heating at 60 °C for 6 h under reflux;

[0115] (3) performing solid-liquid separation to remove free Pd nanoparticles at a centrifugal speed of 7000 rpm;

[0116] (4) After washing with deionized water, the resultant was freeze-dried at -70°C for 8 h to obtain a titanium carbide composite material A3.

[0117] The product obtained in Example 3 was characterized using a scanning electron microscope (brand: Hitachi, model: SU3800). x The SEM image of the nanosheets shows that Ti3C2T x The thickness of the layered nanosheets is about 100nm, which is a multilayer structure (about 40 layers). The SEM image of the Pd nanoparticles shows that the size of the Pd nanoparticles is about 10nm. The SEM image of the titanium carbide composite material shows that the Pd nanoparticles are loaded into the Ti3C2T x The nanosheets' surfaces and interlayers form a composite material.

[0118] In addition, it can be known from the semi-quantitative analysis of EDS energy spectrum that the loading amount of the Pd nanoparticles is 23 wt % relative to the total weight of the titanium carbide composite material.

[0119] Example 4

[0120] 1) Synthesis of Ti3C2T x Nanosheets

[0121] (1) 2 g of Ti3AlC2 powder was placed in 50 ml of hydrofluoric acid (40%) aqueous solution, stirred at room temperature for 36 h, and then centrifuged. After centrifugation, the mixture was washed several times with deionized water until the pH value of the supernatant was 6.

[0122] (2) The product was washed again with deionized water, vacuum filtered using a polytetrafluoroethylene membrane with a pore size of 0.22 μm, and then dried in a vacuum drying oven at 80° C. for 8 h.

[0123] (3) The dried powder was placed in deionized water, ultrasonicated at 4°C, and then separated by a centrifuge to obtain Ti3C2T x Nanosheets.

[0124] 2) Preparation of Pd nanoparticles by sodium citrate reduction method

[0125] (1) 1.0ml / 0.03mol / L H2PdC l4 -tetraethylene glycol solution, 1.0ml / 0.15mol / L polyvinyl pyrrolidone-tetraethylene glycol solution, 1.0ml / 0.045mol / L sodium citrate-tetraethylene glycol solution, and 7.0ml tetraethylene glycol are added to a 50ml round-bottom flask, the flask is connected to a microwave reactor, and the flask is rapidly heated for 60s under rapid stirring with a mechanical stirrer to obtain a polyvinyl alkoxide-stabilized palladium nanoparticle colloidal solution.

[0126] (2) The colloidal solution of palladium nanoparticles changes from brown to dark brown. Five times more acetone is added to the colloidal solution and allowed to stand for a period of time to obtain a viscous black precipitate (its morphology is as shown in FIG. Figure 2 Wash and dry.

[0127] 3) Preparation of titanium carbide composite materials

[0128] (1) Ti3C2T x 0.5 g of nanosheets were dispersed in a dispersion medium with a V (ethanol) / V (water) ratio of 2.5:1 and subjected to ultrasonic treatment; the ultrasonic conditions included: power of 700 W, temperature of 30° C., and time of 240 min;

[0129] (2) adding 0.1 g of Pd nanoparticles, stirring for 2 h in the dark, and then heating at 60 °C for 6 h under reflux;

[0130] (3) performing solid-liquid separation to remove free Pd nanoparticles at a centrifugal speed of 9000 rpm;

[0131] (4) After washing with deionized water, the resultant was freeze-dried at -60°C for 8 h to obtain a titanium carbide composite material A4.

[0132] The product obtained in Example 4 was characterized using a scanning electron microscope (brand: Hitachi, model: SU3800). x The SEM image of the nanosheets shows that Ti3C2T x The thickness of the layered nanosheets is about 90nm, which is a multilayer structure (about 40 layers). The SEM image of the Pd nanoparticles shows that the size of the Pd nanoparticles is about 10nm. The SEM image of the titanium carbide composite material shows that the Pd nanoparticles are loaded into the Ti3C2T x The nanosheets' surfaces and interlayers form a composite material.

[0133] In addition, it can be known from the semi-quantitative analysis of EDS energy spectrum that the loading amount of the Pd nanoparticles is 16 wt % relative to the total weight of the titanium carbide composite material.

[0134] Application Example 1

[0135] Take 2 mg of pineneol in a mortar, add 1 mg of the titanium carbide composite material A1 obtained in Example 1, and grind it thoroughly for 3 minutes. Then use a brush to dip a small amount of material and apply it on the ceramic tube of the interdigitated gold electrode, and then vacuum dry it to form a sensing film to obtain a hydrogen sensor B1. The thickness of the formed sensing film is about 300 μm.

[0136] Application Example 2

[0137] Take 2 mg of pineneol in a mortar, add 1 mg of the titanium carbide composite material A2 obtained in Example 2, and grind it thoroughly for 3 minutes. Then use a brush to dip a small amount of material and apply it on the ceramic tube of the interdigitated gold electrode, and then vacuum dry it to form a sensing film to obtain a hydrogen sensor B2. The thickness of the formed sensing film is about 500 μm.

[0138] Application Example 3

[0139] Take 2 mg of pine oil in a mortar, add 1 mg of the titanium carbide composite material A3 obtained in Example 3, and grind it thoroughly for 3 minutes. Then use a brush to dip a small amount of material and apply it on the ceramic tube of the interdigitated gold electrode, and then vacuum dry it to form a sensing film to obtain a hydrogen sensor B3. The thickness of the formed sensing film is about 600 μm.

[0140] Application Example 4

[0141] Take 2 mg of pineneol in a mortar, add 1 mg of the titanium carbide composite material A4 prepared in Example 4, and grind it thoroughly for 3 minutes. Then use a brush to dip a small amount of material and apply it on the ceramic tube of the interdigitated gold electrode, and then vacuum dry it to form a sensing film to obtain a hydrogen sensor B4. The thickness of the formed sensing film is about 400 μm.

[0142] Comparative Example 1

[0143] Take 2 mg of pineneol in a mortar and add 1 mg of Ti3C2T x The nanosheet material was fully ground for 3 minutes, and a small amount of the material was applied to the ceramic tube of the interdigitated gold electrode with a brush, and then vacuum dried to form a sensing film to obtain a hydrogen sensor D1. The thickness of the formed sensing film was about 500 μm.

[0144] Comparative Example 2

[0145] Take 2 mg of pineneol in a mortar, add 1 mg of Pd nanoparticles prepared in Example 1, and grind thoroughly for 3 minutes. Then use a brush to dip a small amount of material and apply it on the ceramic tube of the interdigitated gold electrode, and then vacuum dry it to form a sensing film to obtain a hydrogen sensor D2. The thickness of the formed sensing film is about 50 μm.

[0146] Test Example 1

[0147] The hydrogen sensors B1-B4 prepared by using the titanium carbide composite materials in Examples 1-4 are as follows: Figure 5 The minimum detection limits of hydrogen for each sensor B1-B4 are close, all about 1%. x The hydrogen sensor D1 made of nanosheet material, the hydrogen sensor D2 made of Pd nanoparticles in Comparative Example 2, and the hydrogen sensor B1 made of titanium carbide composite material in Example 1 were placed in 5% concentration of hydrogen, and the resistance value changes were as follows: Figure 4 As shown in curves (1), (2) and (3), the performance of B1 is significantly better than that of D1 and D2.

[0148] Depend on Figure 4 It can be seen that the hydrogen sensor made of titanium carbide composite material can detect hydrogen quickly (within 10S) and with high sensitivity at room temperature, and the response has good reversibility.

[0149] Depend on Figure 4 The comparison of the middle curve shows that the hydrogen sensing performance of titanium carbide composite material is better than that of single component Ti3C2T x Nanosheets, Pd nanoparticles.

[0150] Test Example 2

[0151] Test Application Example 1: The response of the hydrogen sensor made of the titanium carbide composite material to the interfering gas.

[0152] Interfering gases include: hydrogen sulfide, methane, carbon monoxide, and nitric oxide.

[0153] The hydrogen sensor was placed in hydrogen sulfide gas of different concentrations. The results showed that at the same concentration, the response intensity of hydrogen sulfide was only 1% of the response intensity of hydrogen.

[0154] The hydrogen sensor was placed in methane gas of different concentrations. The results showed that at the same concentration, the response intensity of methane was only 0.8% of the response intensity of hydrogen.

[0155] The hydrogen sensor was placed in carbon monoxide gas with different concentrations. The results showed that at the same concentration, the response intensity of carbon monoxide was only 0.8% of the response intensity of hydrogen.

[0156] The hydrogen sensor was placed in different concentrations of nitric oxide gas. The results showed that at the same concentration, the response intensity of nitric oxide was only 0.8% of the response intensity of hydrogen.

[0157] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A titanium carbide composite material, characterized in that: The titanium carbide composite material comprises Ti3C2T x Substrate and load on the Ti3C2T x The Pd nanoparticles on the substrate, the Ti3C2T x The substrate has a multilayer structure, and at least part of the Pd nanoparticles are loaded on the Ti3C2T x Between the layers of the base multi-layer structure.

2. The titanium carbide composite material according to claim 1, wherein The multi-layer structure has 30-80 layers; Preferably, the Ti3C2T x The substrate thickness is 5-150 nm, preferably 10-100 nm.

3. The titanium carbide composite material according to claim 1, wherein The particle size of the Pd nanoparticles is 5-80 nm, preferably 5-40 nm.

4. The titanium carbide composite material according to any one of claims 1 to 3, wherein: The loading amount of the Pd nanoparticles is 10-60 wt % relative to the total weight of the titanium carbide composite material.

5. The titanium carbide composite material according to claim 2 or 3, wherein: The Pd nanoparticles are loaded on the Ti3C2T x Substrate surface and the Ti3C2T x Between the layers of the base multi-layer structure.

6. A method for preparing a titanium carbide composite material, characterized in that: The method comprises: in a light-proof condition, making a Ti3C2T x After the dispersion of nanosheets is brought into contact with the Pd nanoparticles, the product after the contact is subjected to a solid-liquid separation step.

7. The method according to claim 6, wherein: The Ti3C2T x The dispersion of nanosheets was prepared by mixing Ti3C2T x The nanosheets are dispersed in a dispersion medium; Preferably, by x The nanosheets are dispersed in a dispersion medium and then subjected to ultrasound to obtain; Preferably, the ultrasonic conditions include: power of 100-800W, temperature of 0-30°C, and time of 60-600min; Preferably, Ti3C2T x The weight ratio of nanosheets to dispersion medium is 1:50-100; Preferably, the dispersion medium is one or more of water, ethanol, acetone and n-hexane; Preferably, the dispersion medium is water and ethanol; Preferably, the volume ratio of ethanol to water is 1-5:1, preferably 1-3:

1.

8. The method according to claim 6, wherein: The Pd nanoparticles and Ti3C2T x The weight ratio of the nanosheets is 0.1-0.6:1, preferably 0.1-0.3:1; Preferably, the contacting conditions include: temperature of 60-80° C. and time of 6-12 h.

9. The method according to any one of claims 6 to 8, wherein: The solid-liquid separation is centrifugal, and the speed of the centrifugal is 3000-15000 rpm, preferably 6000-10000 rpm; Preferably, the method further comprises the step of freeze-drying the solid phase obtained by solid-liquid separation; Preferably, the method further comprises the step of washing the solid phase obtained by solid-liquid separation with water before freeze-drying; Preferably, the freeze-drying conditions include: a temperature of -70 to -40°C and a time of 6 to 14 hours.

10. The method according to any one of claims 6 to 8, wherein: The Ti3C2T x The nanosheets are obtained by etching the precursor Ti3AlC2 using hydrofluoric acid or fluoride salts.

11. The method according to any one of claims 6 to 8, wherein: The Pd nanoparticles are reduced to H2PdC by a reducing agent l4 It is obtained by Pd ions in solution.

12. The method according to claim 11, wherein: The reducing agent is one or more of hydrazine hydrate, sodium citrate and sodium borohydride, preferably sodium citrate or sodium borohydride.

13. A hydrogen sensor, characterized in that: The hydrogen sensor comprises: a sensing film formed on the surface of an electrode, wherein the sensing film contains the titanium carbide composite material according to any one of claims 1 to 5 or the titanium carbide composite material prepared by the method according to any one of claims 6 to 12.

14. A method for preparing a hydrogen sensor, characterized in that: The method comprises the step of coating the titanium carbide composite material described in any one of claims 1 to 5 or the titanium carbide composite material prepared by the method described in any one of claims 6 to 12 on the surface of an electrode to form a sensing film.

15. The method according to claim 14, wherein: The titanium carbide composite material is dispersed and ground using an organic solvent, and the ground material is coated on the surface of the electrode to form a sensing film; Preferably, the mass ratio of the organic solvent to the titanium carbide composite material is 1-5:1, preferably 1-3:

1.

16. The hydrogen gas sensor according to claim 14 or 15, wherein: The thickness of the sensing film is 50-2000 μm, preferably 100-1000 μm.

17. Use of the titanium carbide composite material according to any one of claims 1 to 5 or the titanium carbide composite material prepared by the method according to any one of claims 6 to 12 in preparing a hydrogen sensor.

Citation Information

Patent Citations

  • Two-dimension carbide loaded metal simple substance nano-powder, and preparation method and application thereof

    CN105854913A

  • Method for preparing novel titanium carbide / palladium / platinum nanocomposite material

    CN108398469A

  • Preparation method of platinum-palladium dispersion modified two-dimensional material hydrogen sensor

    CN115808454A

  • Multi-doped two-dimensional supported metal material, preparation method and application of multi-doped two-dimensional supported metal material in fuel cell

    CN116666654A

  • Hydrogen sensor based on paladium-graphene nanocomposite and method of fabricating the same

    KR1020140134172A